Kedudukan Notaris Yang Mengambil Cuti Karena Diangkat Menjadi Anggota Legislatif - Astra Vigo Putra; Elita Rahmi; Firdaus Abu Bakar (Magister Kenotariatan, Universitas Jambi, 2023)
The duty of a notary as a public official is to serve the public concerned. As a servant, of course, a very noble task borne by a Notary. By referring to the UUJN which is actually a regulation that regulates his position, according to the author, it does not violate the law if it overrides the election law regarding concurrent positions. And also no party will be harmed if a Notary who is a member of the DPR applies for leave, in other words it does not stop. Notaries are required to apply for leave, and appoint a substitute Notary as stated in Article 11 paragraph (1-3) of the UUJN if the Notary is elected as a member of the Legislature. Because based on Article 17 letter d of the UUJN, a Notary is prohibited from serving as a state official. Regarding the request for leave due to being appointed as a State Official, the MPP must have received it within a maximum period of 60 (sixty) days from the date the decision as a State Official is stipulated. Before a Notary submits an application for leave, the mechanism in applying for a Notary leave that needs to be done first is to apply for a Leave certificate to the Directorate General of AHU Online. The request for leave must be received by the Regional Supervisory Council, Regional Supervisory Council, or Central Supervisory Council at the latest 30 (thirty) days before the leave is implemented, unless there are other valid reasons. Abstrak Tugas Notaris sebagai pejabat umum ialah melayani masyarakat yang berkepentingan. Sebagai pelayan, tentunya sangat mulia tugas yang dipikul oleh Notaris. Dengan mengacu terhadap UUJN yang notabene sebuah peraturan yang mengatur akan jabatannya, menurut penulis tidak melanggar hukum apabila mengesampingkan Undang-undang pemilu soal rangkap jabatan. Dan juga tidak ada pihak yang dirugikan apabila Notaris yang menjadi anggota DPR mengajukan cuti, dengan kata lain tidak berhenti. Notaris wajib mengajukan cuti, dan menunjuk Notaris pengganti seperti yang disebutkandalamPasal 11 ayat (1-3) UUJN apabilaNotaris terpilih menjadi anggota Legislatif. Karena berdasarkan Pasal 17 huruf d UUJN Notaris di larangrangkap jabatan menjadi pejabat negara. Mengenai permohonan cuti karena diangkat menjadi Pejabat Negara harus sudah diterima MPP dalam jangka waktu paling lama 60 (enam puluh) hari sejak tanggal keputusan sebagai Pejabat Negara ditetapkan. Sebelum Notaris mengajukan permohonan cuti, mekanisme dalam pengajuan cuti Notaris yang perlu dilakukan terlebih dahulu ialah mengajukan permohonan sertifikat Cuti kepada Direktorat Jendral AHU Online. Permohonan cuti sudah harus diterima oleh Majelis Pengawas Daerah, Majelis Pengawas Wilayah, atau Majelis Pengawas Pusat dalam jangka waktu paling lambat 30 (tiga puluh) hari sebelum cuti dilaksanakan, kecuali ada alasan lain yang sah.